An integrated closed-tube 2-plex PCR amplification and hybridization assay with switchable lanthanide luminescence based spatial detection. Issue 12 (21st June 2015) - Lahdenperä, Susanne; Spangar, Anni; Lempainen, Anna-Maija; Joki, Laura; Soukka, Tero
<x xml:space="preserve">Abstract</x> A proof-of-principle of a genuine closed-tube nucleic acid assay with integrated 2-plex PCR amplification and array-based detection has been presented.